2015
DOI: 10.1080/21645515.2015.1102811
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal serotype distribution in adults with invasive disease and in carrier children in Italy: Should we expect herd protection of adults through infants' vaccination?

Abstract: The 7-valent pneumococcal conjugate vaccine (PCV7) produced a significant herd protection in unvaccinated adult population mostly because of pneumococcus carriage decrease in vaccinated children. It is not known if the 13-valent pneumococcal vaccine can give similar effect on adults. Aims of the work were to evaluate whether the 6 additional serotypes are present in nasopharynx of children and serotype distribution in invasive pneumococcal infections (IPD) in adults.  Realtime-PCR was used to evaluate pneumoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…12,17 All these studies support the possible presence of a S. pneumoniae reservoir outside vaccinated children, an observation also made by other authors. 12,17,31 Non-PCV serotypes…”
Section: What About Ppv-23 On the Ipd And Carriage?supporting
confidence: 68%
See 1 more Smart Citation
“…12,17 All these studies support the possible presence of a S. pneumoniae reservoir outside vaccinated children, an observation also made by other authors. 12,17,31 Non-PCV serotypes…”
Section: What About Ppv-23 On the Ipd And Carriage?supporting
confidence: 68%
“…However, this is not the case for some of the PCV serotypes when looking at the elderly in particular. 12,17 Studies have shown that there does not seem to be a hidden circulation of PCV serotypes carried in vaccinated infants, while PCV serotypes still contribute to IPD in unvaccinated individuals. 31 It has also been shown that some of the additional PCV-13 serotypes are still a major cause of IPD in the group of elderly persons, and that vaccination of children with PCV-13 has not shown a reduction in IPD with these serotypes in this age group.…”
Section: What About Ppv-23 On the Ipd And Carriage?mentioning
confidence: 99%
“…Similarly to our findings, other studies, performed in Wales and England, demonstrated that few years after PCV13 implementation a reduction of 32% of VT IPD was observed, but this decrease did not generate a high impact on the general pneumococcal disease incidence (VT and NVT) due to an increase of NVT diseases. 20,21 The increased incidence of pneumococcal disease could be related to the rise of the hospitalization rate observed in the older age groups (adult and the elderly), also demonstrated by Amodio at al., 17 for specified pneumococcal pneumonia and by Azzari e al., 23 revealing a progressive increase in the incidence of IPD in adults, particularly in the elderly, aged 61–75 y. Probably, the highest incidence of the disease in the elderly population must be related to a higher prevalence of co-morbidity in this subjects rather than in younger age groups and to the influence of other factors, such as lifestyle or confounding factors (eg, smoking prevalence in the general population, influenza vaccination coverage).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on pneumococcal colonization in children have been widely undertaken [ 21 , 27 , 28 , 29 ]. However, the contribution of PCV immunized children to bacterial spread among their unvaccinated co-habiting relatives has not been investigated so far.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported that high rates of vaccination coverage in childhood may result in the herd immunity among unvaccinated subjects, protecting against disease caused by serotypes included in vaccine formulations [ 21 ], but also preventing nasopharyngeal colonization [ 22 ].…”
Section: Introductionmentioning
confidence: 99%